2019
DOI: 10.3390/ijms20205090
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols: A Multifactorial Strategy to Target Alzheimer’s Disease

Abstract: Ageing is an inevitable fundamental process for people and is their greatest risk factor for neurodegenerative disease. The ageing processes bring changes in cells that can drive the organisms to experience loss of nutrient sensing, disrupted cellular functions, increased oxidative stress, loss of cellular homeostasis, genomic instability, accumulation of misfolded protein, impaired cellular defenses and telomere shortening. Perturbation of these vital cellular processes in neuronal cells can lead to life thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 361 publications
0
52
1
Order By: Relevance
“…Diets are often implicated in AD, and various studies have shown protective effects of bioactives to neuronal cells. However, unlike prescription drug studies, it is hard to obtain rigorous data to support dietary interventions [16].…”
Section: Yeast Strains Plasmids and Growth Mediamentioning
confidence: 99%
“…Diets are often implicated in AD, and various studies have shown protective effects of bioactives to neuronal cells. However, unlike prescription drug studies, it is hard to obtain rigorous data to support dietary interventions [16].…”
Section: Yeast Strains Plasmids and Growth Mediamentioning
confidence: 99%
“…The cellular environment with a higher level of NAD + activates SIRT1 expression and SIRT1-mediated deacetylation of its targets [285]. In mammals, another important target of SIRT1 is transcription factor EB (TFEB), the master regulator of lysosome biogenesis and autophagy [2]. In addition, DNA damage, metabolic stress, and oxidative damage of cells activates tumor suppressor protein p53 mediated activation of autophagy and cell cycle arrest [286].…”
Section: Conservation Of Autophagy Regulation In Yeast Modelsmentioning
confidence: 99%
“…AD is characterized by the accumulation of unwanted toxic protein aggregates including tau neurofibrillary tangles and Aβ aggregates (oligomers, fibrils, and senile plaques) [2]. From previous studies, it has been found that the protein quality control and the cellular defense system has failed severely during AD progression [348].…”
Section: Proteostasis Failure In Admentioning
confidence: 99%
See 2 more Smart Citations